2022
DOI: 10.1371/journal.pgph.0000116
|View full text |Cite
|
Sign up to set email alerts
|

Pooling sputum for Xpert MTB/RIF and Xpert Ultra testing during the Covid-19 pandemic in Lao People’s Democratic Republic

Abstract: The global Covid-19 pandemic has limited access to molecular TB diagnostics and National Programmes are struggling to maintain essential services. The pooling method (testing several samples together) could reduce the number of cartridges and staff time needed for TB diagnosis but has not been tested within the pandemic. We conducted two independent cross-sectional surveys. Pools composed of four sputum samples were tested using either Xpert-MTB/RIF or Xpert-Ultra. Pooled and individual results were compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In 2015, due to drug resistance rising worldwide, the WHO proposed expanding rapid testing and detection of cases as one of the five high-priority actions to tackle the global DR-TB crisis [15]. As part of these actions, some molecular biology-based diagnostic methods have been applied in a clinical setting for their versatility and speed, including variants of Xpert MTB/RIF and Geno-Type MTBDRplus [16][17][18][19]. Although these methods are rapid and straightforward, Mtb continuously evolves through the genomic acquisition of single nucleotide polymorphisms (SNPs), insertions, and deletions (indels), impacting the ability to discriminate strains without the classic regions used for resistance detection [20].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, due to drug resistance rising worldwide, the WHO proposed expanding rapid testing and detection of cases as one of the five high-priority actions to tackle the global DR-TB crisis [15]. As part of these actions, some molecular biology-based diagnostic methods have been applied in a clinical setting for their versatility and speed, including variants of Xpert MTB/RIF and Geno-Type MTBDRplus [16][17][18][19]. Although these methods are rapid and straightforward, Mtb continuously evolves through the genomic acquisition of single nucleotide polymorphisms (SNPs), insertions, and deletions (indels), impacting the ability to discriminate strains without the classic regions used for resistance detection [20].…”
Section: Introductionmentioning
confidence: 99%
“…In this cost-effectiveness analysis, a total of 3,076 individuals with presumptive TB were enrolled from two studies conducted in Lao PDR (840 individuals per study) [ 8 ], two studies in Nigeria (500 individuals per study) (Bimba et al in press), and one study in Brazil (396 individuals) [ 9 ], which are described in more detail below.…”
Section: Methodsmentioning
confidence: 99%
“…In Lao PDR [ 8 ] and Nigeria (Bimba et al in press), two independent studies were conducted during PCF of people with presumptive TB, one using Xpert MTB/RIF, and the other Ultra. The study from Brazil assessed the performance of pooled testing with Xpert Ultra only [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a systematic review of studies where each specimen was tested both individually and in pools, Cuevas et al reported that the positive percent agreement for pools of four samples as compared with individual samples was 91% for the Xpert MTB/RIF assay and 98% for the Xpert MTB/RIF Ultra assay 39 . Subsequent studies have reported similarly small reductions in testing accuracy with large improvements in testing efficiency and significant cartridge and cost savings when using these assays for pooled testing for TB detection 36 , 37 , 40 . However, despite these results that highlight the good potential value of pooled testing to improve the detection of TB, pooled testing has not yet been widely adopted to increase molecular testing coverage for routine TB diagnosis.…”
Section: Introductionmentioning
confidence: 92%